Immunomodulatory, Anticancer, and Antimicrobial Effects of Rice Bran Grown in Iraq: An In Vitro and In Vivo Study - Wamidh H. Talib; Asma Ismail Mahmod; Dima Awajan; Reem Ali Hamed; Intisar Hadi Al-Yasari (MDPI AG, 2022)
Emerging evidence supports the role of rice bran in cancer prevention. Studies were conducted on multiple rice cultivars. However, limited studies were conducted on rice cultivars in the Middle East. In this study, rice bran growing in Iraq (O. sativa ssp. Japonica, cultivars: Amber Barka) was evaluated for its effect on preventing cancer and stimulating the immune system. Rice bran was collected from local mills in Al-Najaf (south of Iraq). Several solvent extracts (ethanol, methanol, n-hexane, and water) were prepared by maceration. MTT assay was used to measure the antiproliferative effects of extracts against a panel of cancer cell lines. The ability of each extract to induce apoptosis and inhibit angiogenesis was measured using standard ELISA kits. The effect of extracts on the immune system was evaluated using a lymphocyte proliferation assay, a pinocytic activity assay, a phagocytic activity assay, and a Th1/Th2 cytokine detection kit. A microbroth dilution method was used to detect the antimicrobial activity of each extract against different microbial strains. LC-MS analysis was used to detect the phytochemical composition of extracts, while DPPH assay was used to determine the antioxidant activity. For the in vivo study, rice bran was added to mouse fodder at 10% and 20%. Mice were treated for two weeks using mouse fodder supplemented with rice bran. In the third week of the experiment, EMT6/P breast cancer cells (1 × 10⁶ cells/mL) were injected subcutaneously into the abdominal area of each mouse. The dimensions of the grown tumors were measured after 14 days of tumor inoculation. A microbroth dilution method was used to evaluate the antimicrobial activity of rice bran extracts against three bacterial strains. The highest antiproliferative activity was observed in ethanol and n-hexane extracts. Ethanol and methanol extract showed the highest activity to induce apoptosis and inhibit angiogenesis. Both extracts were also effective to enhance immunity by activating lymphocytes and phagocytes proliferation with modulations of cytokine levels. The incorporation of rice bran in mice food caused a 20% regression in tumor development and growth compared with the negative control. All extracts exhibited limited antimicrobial activity against tested microorganisms. Methanol extract showed antioxidant activity with an IC50 value of 114 µg/mL. LC-MS analysis revealed the presence of multiple phytochemicals in rice bran including apiin, ferulic acid, and succinic acid. Rice bran is a rich source of active phytochemicals that may inhibit cancer and stimulate the immune system. Rice bran's biological activities could be due to the presence of multiple synergistically active phytochemicals. Further studies are needed to understand the exact mechanisms of action of rice bran.